Fast screening of the fatigue properties of thermoplastics reinforced with short carbon fibers based on thermal measurements. (July 2018) - Leveuf, L.; Marco, Y.; Le Saux, V.; Navrátil, L.; Leclercq, S.; Olhagaray, J.
Abstract: The goal of this paper is to investigate the ability of the heat build-up technique to predict the fatigue lifetime of injected thermoplastic reinforced with short carbon fibers. Several commercial grades and filler ratios are considered in order to challenge the ability of the technique to capture the influence of these variations. First, the materials are investigated and the mechanical and thermal protocols are described. The way to build the heat-build-up curves is outlined. Then, the results obtained from the heat build-up and fatigue experiments are presented. The heat build-up curves are obtained both from measurements performed on the front surface of the sample and from the side surface. Finally, these results are used to discuss two main points. The first is the validity of the hypotheses needed to apply the approach, ranging from the evaluation of the dissipation to the fatigue response. The second is the capability to predict the fatigue curves accurately through an energetic criterion, and to identify the influence of the variations of matrix grade and fiber content on the fatigue properties. It appears that the predictions obtained match the results obtained from classic fatigue tests and validates the use of the technique for fast material screening.